Food additives - second edition - Branen, A. Larry (Marcel Dekker, 2011)
This book, volume 114 in the series Food Science and Technology, emphasises the biochemical, chemical, and toxicological components of numerous food additives as well as their benefits and risks. Offering over 2000 useful references and more than 200 helpful tables, equations, drawings, and photographs, this book presents research on food phosphates, commercial starches, antibrowning agents, essential fatty acids, and fat substitutes, as well as studies on consumer perceptions of food additives. With contributions from nearly 50 leading international authorities, the Second Edition of Food Additives details food additives for special dietary needs, contemporary studies on the role of food additives in learning, sleep, and behavioral problems in children, safety and regulatory requirements in the U.S. and the European Union, and methods to determine hypersensitivity. It will be of value to food scientists, chemists, and technologists; nutritionists, dieticians, toxicologists, agricultural scientists, microbiologists, and biochemists; food and drug administrators, food quality assurance and safety inspectors, and public health professionals as well as advanced undergraduate and graduate students of food science and related disciplines.